Aging in Zimbabwe: Reflections 41 Years After Independence - Hungwe, Chipo (Oxford University Press, 2022)
While Zimbabwe shares similar characteristics with other sub-Saharan countries that are generally regarded as “young populations,” the percentage of older adults has increased from 4.7% in 1982 to 6% in 2017. Research on aging is mainly on social protection, health, and quality of life. Emerging research points toward healthy aging, gender relations, and access to resources. The economic environment has been unstable for the greater part of the 41 years of independence. Poverty is increasing and the lives of older adults are vulnerable owing to inadequate and poorly targeted and funded social safety nets and social care services. The framework for addressing aging in the country is adequate but implementation is lacking. Zimbabwe lacks longitudinal data sets on aging; researchers mostly rely on data produced by Zimbabwe National Statistics Agency, United Nations agencies, and other international nongovernmental organizations.